2020 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2020)
This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, use and costs of care, and the overall impact on caregivers and society. The Special Report discusses the future challenges of meeting care demands for the growing number of people living with Alzheimer's dementia in the United States with a particular emphasis on primary care. By mid‐century, the number of Americans age 65 and older with Alzheimer's dementia may grow to 13.8 million. This represents a steep increase from the estimated 5.8 million Americans age 65 and older who have Alzheimer's dementia today. Official death certificates recorded 122,019 deaths from AD in 2018, the latest year for which data are available, making Alzheimer's the sixth leading cause of death in the United States and the fifth leading cause of death among Americans age 65 and older. Between 2000 and 2018, deaths resulting from stroke, HIV and heart disease decreased, whereas reported deaths from Alzheimer's increased 146.2%. In 2019, more than 16 million family members and other unpaid caregivers provided an estimated 18.6 billion hours of care to people with Alzheimer's or other dementias. This care is valued at nearly $244 billion, but its costs extend to family caregivers’ increased risk for emotional distress and negative mental and physical health outcomes. Average per‐person Medicare payments for services to beneficiaries age 65 and older with AD or other dementias are more than three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 23 times as great. Total payments in 2020 for health care, long‐term care and hospice services for people age 65 and older with dementia are estimated to be $305 billion. As the population of Americans living with Alzheimer's dementia increases, the burden of caring for that population also increases. These challenges are exacerbated by a shortage of dementia care specialists, which places an increasing burden on primary care physicians (PCPs) to provide care for people living with dementia. Many PCPs feel underprepared and inadequately trained to handle dementia care responsibilities effectively. This report includes recommendations for maximizing quality care in the face of the shortage of specialists and training challenges in primary care.